STUDY ON INDONESIAN LANGUAGE POLITENESS OF THE STUDENTS AT THE INDONESIAN LANGUAGE AND LITERARY EDUCATION STUDY PROGRAM UNIVERSITAS MUHAMMADIYAH MAKASSAR - Wahyu Ningsih; Nur Khadijah Razak (Universitas Sembilanbelas November Kolaka, 2017)
This study discusses the descriptions of the use and deviation of the principle of Indonesian politeness in the Campus of Muhammadiyah University of Makassar. This research was conducted in two stages, namely data collection and data analysis phase. Stage of data collection was conducted in a form of field research to get primary data by using observation technique through data card, while at data analysis phase the reserachers used qualitative descriptive analysis. The analysis was used to obtain a description of the form of maxim application in the conversation of the students of Muhammadiyah University of Makassar. The result of the research showed that the element of language politeness was still less applied in the conversation of the student. This indicated that there were various factors that accompanied the communication process. Among these were the situation of conversation, the object being discussed, the individual user of the language involved, less able to see the suitability and accuracy of vocabulary usage in the conversation. This could be seen from the use and the maximal deviation in the conversation through the principle of language politeness proposed by Leech, including maxim of wisdom, maxim of acceptance, maxim of generosity, maxim of humility, maxim of agreement, and maxim of sympathy.